Incidence and Risk Factors of Immediate Complication after Transthoracic Needle Biopsy of Pulmonary Lesions at Songklanagarind Hospital - Tiraphat Kosawiwat; Sitang Nirattisaikul; Jitpreedee Sungsiri; Keerati Hongsakul (Journal of Health Science and Medical Research (JHSMR), 2016)
Objective: To evaluate the incidence, the type and the risk factors of complications from transthoracic needle biopsies of pulmonary lesions at Songklanagarind Hospital. Material and Methods: We analyzed the data from 182 patients who had undergone 131 fluoroscopically guided and 69 computed tomography guided lung biopsies at Songklanagarind Hospital from June 2011 to June 2012. The incidence and type of complications were determined. The risk factors for complications were evaluated using multivariate logistic regression analysis. P-value less than 0.05 was considered statistically significant. Results: The overall incidence of complications was 22.5%.The most common complication was pneumothorax (15.5%) and the second most common was hemoptysis (8.5%). Severe complications in this study were less frequent including chest tube placement for pneumothorax (4.5%) and endotracheal intubation for hemoptysis (1%). The significant risk factors in the CT guided biopsy group were lesion characteristic and greater lesion depth. Lesion characteristic was also the significant risk factor in the fluoroscopically guided biopsy group. Conclusion: The most common complication after transthoracic needle biopsy was pneumothorax. The predominant risk factors included ill-defined lesion and greater lesion depth.